Comparative study on fiber laser welding of GH3535 superalloy in continuous and pulsed waves. (15th November 2016) - Jiang, Zhenguo; Tao, Wang; Yu, Kun; Tan, Caiwang; Chen, Yanbin; Li, Liqun; Li, Zhijun
Abstract: GH3535 superalloy is the candidate structural material for the next-generation nuclear reactors and its related welding problem is inevitable and needs to be solved. In this work, fiber laser welding of 4-mm-thick GH3535 superalloy in continuous wave (CW) and pulsed wave (PW) was comparatively investigated. The weld appearances, dynamic behavior of weld pool, microstructure and mechanical properties in both cases were studied. The results indicated that larger porosities were present in the bottom of the CW joint while few porosities appeared in the PW joint. The laser weld zone of both CW and PW joints was still composed of γ-Ni matrix and M6 C carbides. Grain size of PW joint was smaller than that of CW joint. More precipitated particles were found in the PW joint. The presence of porosity in the CW joint reduced mechanical properties greatly. The tensile strength decreased to 85% of that of base metal at room temperature, and 82.3% at high temperature while the PW joint strength could reach 97.6% and 95.7% at room and high temperature, respectively. The fracture surface of CW joint had a flat pattern and porosities, while PW joint exhibited dimples on the fracture surface both at room and high temperature. Graphical abstract: Highlights: Laser welding characteristics of new GH3535 alloy of TMSR was studied. Comparative study of laser welding in continuous and pulsed waves Porosity rate and molten dynamics at both cases were investigated. Pulsed welding produced finer microstructure and more precipitated particles. Superalloy welded joints at room and high temperature were evaluated.